Family Size and the Age at Infancy-Childhood Transition Determine a Child’s Compromised Growth in Large Families - German, Alina; Rubin, Lisa; Raisin, Galiya; Hochberg, Ze’ev (Frontiers in Pediatrics, 2022)
Background: Data on growth of Israeli school children show that children from Jewish ultra-orthodox Haredi and Bedouin Arab families have a higher prevalence of stature below the 3rd percentile.[1]. While these populations are usually from lower socioeconomic strata, they also have larger families. This study aimed to evaluate if family structure and the timing of a child’s infancy–childhood transition (ICT) are central to variations in stature. Study design: We analyzed the association between family size, birth order and inter-birth interval with child growth and the age at ICT in 3 groups of children, 148 high birth order children from large families (LF ≥6 ), 118 low birth order children from large families (LF ≤3) and 150 children from small families (SF). Results: High birth order children from large families were shorter in childhood than children from small families with a difference of 0.5 SDS in length. We found that birth length and birth order explained 35% of the total variance in infancy length whereas ICT age and infancy length explained 72% of the total variance in childhood length. Conclusions: Infancy and childhood length are compromised in children from large families. As the family grows larger the younger children tend to be shorter. Reduced length gain in the period between infancy to childhood is when growth is most affected.